THE EFFECT OF PLASTIC WASTE AS SOIL STABILIZATION FOR SHALLOW FOUNDATIONS USING DIRECT SHEAR TEST - Safa Sabitah Rasikah Utomo; Dandung Novianto; Mohamad Zenurianto (Jurusan Teknik Sipil Politeknik Negeri Malang, 2025)
Expansive clay soil are types of soils that show a significant change in volume once they contact with moisture and structure built on this soil are highly vulnerable due to the swelling and shrinking behavior. Stabilization of soil is required to keep the quality of soil to be used for the foundation work within allowable limits. The material used in this research for soil stabilization is PET plastic because it is one of the most commonly recycled types of plastic. This research aims to determine the classification of soil in Temas village, Batu, East Java based on the USCS classification system and to determine the values of c and f with the addition of plastic size variations of 0,5 cm x 1 cm; 0,75 cm x 1,25 cm; and 1 cm x 1,5 cm at 0,75%; 1,5%; and 2,5%. Soil in Temas villages included in the SP-SC soil type, namely poorly graded sand and clayey sand. From the soil stabilization tests using plastic waste, there is a tendency for improvement. However, the shear angle decreases with increasing percentages of PET waste. The highest shear angle value occurred in stabilization with plastic size 1 cm x 1,5 cm at 0,75%, measuring 49,73°. The highest cohesion value was 0,844 kg/cm2 obtained from plastic size 0,5 cm x 1 cm at 1,50%. For the allowable load (Qall) with plastic mixture shows significant improvement. The highest allowable occurs in rectangular shape with size of 1 m x 1,5 m. For original soil can only support a maximum load 37,30 tons and the highest allowable load observed in the mixture of original soil + plastic size 1 cm x 1,5 cm at 0,75%, which is 1.382,28 tons. The work carried out are excavation work, sand fill work, lean concrete work, soil mix with plastic waste, compaction work, concrete work, reinforcement work, and formwork with tools used are concrete mixer and manual equipment. The cost estimate for a rectangular foundation is Rp 46.336.177,01.